Formação de professores no ciberespaço: a gestão dos cursos de licenciatura, modalidade à distância, no Instituto Federal De Educação, Ciência e Tecnologia da Paraíba (IFPB) - Silva, Gerlane Barbosa da (2017)
The complexity of globalization process and advancement of digital information and communication technologies have changed the ways of life in contemporary society. The formation of the thought and the teaching-learning processes on the Brazilian educational system on the 21st century - a century marked by the height of Cyberculture - is influenced by the reflexes of the digital culture’s plots, threads and nodes. In this context, the system of distance education (EaD) presents itself as a teaching modality favorable to the expansion of higher education in Brazil. Also, professor training is promoted through this modality of education. In this scenario, the "Rede Federal de Educação, Ciência e Tecnologia" is also established as basis to the training of professors by offering degrees and instigating us to understand how this Network is helping training professors. Since, historically, it was constituted to technical-vocational education. Thus, the aim of the present research is to understand the management of undergraduate courses (teacher training) offered the system of distance education (EaD) at the Federal Institute of Education, Science and Technology of Paraíba (IFPB). The methodology used was field research with a qualitative and exploratory approach by using a semi-structured interview as a data collection instrument applied to IFPB managers. For data collection we used documentary research, specifically aimed at the Pedagogical Projects of Courses (PPC) and the Institutional Development Plan (PDI). The interpretation of the datas were based on content analysis. The IFPB offers the undergraduate course in Computing and Computer Science linked to the Open University of Brazil (UAB) and the Letters' graduation executed institutionally by EaD. The distance learning courses of the IFPB present a curricular structure in accordance with national regulations, which allow them promote training to their professors related with the professional profile of the professors. It includes various dimensions of training through well-defined evaluation methodologies and evaluation procedures in process of improvement. The institutional Letters' graduation is a pioneer on offering the distance graduation among the Federal Institutes. It is an unique initiative in the reality of the IFPB and it has been a model for other institutions in the Federal System, especially with their personalized teaching materials and the fact that their professors are from the staff team of the own institution. The undergraduate course in Letters - institutional and pioneering - shows itself as a unique initiative. Also, a model for the Federal Network itself. It has personalized instructional material (didactic-pedagogical) and teaching staff of the institution's permanent staff. The IFPB sees the EaD as a promising path for education in the current society, therefore there is a planning to promote this modality. The Computing and Informatics’ graduation has external financial support, uses physical structure of the municipalities' poles and temporary professionals. The Letters' graduation has all the physical, administrative and personnel structure of the Federal System of Education to execute its courses independently of external announcements and of pre-established periods. Therefore, it is possible to understand that the management of the undergraduate courses of the EAD at the IFPB is committed to sake and demands of professionals of basic education. So far, it has been achieved by promoting courses focused on teaching, but has potential of development and consolidation in the Federal System of Education.